Implementation of an Elemental Diet in Five Children Diagnosed with Autism Spectrum Disorder Presenting with Gastrointestinal Disease: A Brief Report - Barnhill, Kelly; Gutierrez, Alan; Potts, Amy; Devlin, Morgan; Richardson, Wendy; Hewitson, Laura (International Journal of Nutrition, 2020)
Autism Spectrum Disorder (ASD) is a developmental disorder characterized by impaired communication and social interaction. Children with ASD are frequently diagnosed with gastrointestinal (GI) issues, including inflammatory bowel disease (IBD), gastroesophageal reflux, abdominal pain, diarrhea, and constipation, although the association between ASD and GI conditions is unclear. Underlying nutritional deficiencies are more common in children with ASD, and increase the risk of them developing medical conditions secondary to the behavioral diagnosis. This objective of this study was to examine the use of an elemental diet (ED) in the treatment of gastrointestinal disease in 5 children with ASD ages 2-21 years of age. In the study participants, the ED was well-tolerated with improvements in anthropometric measures, nutritional markers, and/or GI functioning reported after 12 weeks of intervention. Further research to advance the development of specific evidence-based guidelines in the management and treatment of gastrointestinal concerns in the ASD population is warranted.
Keywords: nutrition; elemental diet; autism spectrum disorder; gastrointestinal; anthropometrics; pediatric; intervention